You really should proofread what you post. I'll go with
-x^2 - 4x + 12
-(x^2 + 4x) + 12
-(x^2 + 4x + 4) + 12 + 4
-(x+2)^2 + 16
-x^2 - 4x + 12
-(x^2 + 4x - 12)
-(x+6)(x-2)
There are lots of handy online graphing sites if you need help with that.
Express f(x) = -x-4x+ 12 in the vertex form, fix) = ax + h)²+ k, and in the intercept form, flx)= a(x + p)(x +q). where a, h, k, p and q are constants. Hence, sketch the graph..
2 answers
If your question means:
Express f(x) = - x² - 4 x + 12
then
add and subtract 4 to left side
f(x) = - x² - 4 x + 12 + 4 - 4
f(x) = - x² - 4 x - 4 + 12 + 4
f(x) = - ( x² + 4 x + 4 ) + 16
f(x) = - ( x² + 2 ∙ x ∙ 2 + 2² ) + 16
Since:
( a + b )² = a² + 2 ∙ a ∙ b + b²
( x + 2 )² = x² + 2 ∙ x ∙ 2 + 2²
f(x) = - ( x + 2 )² + 16
f(x) = a ( x - p ) ( x - q )
where p and q are the roots:
In this case:
a = - 1
- ( x + 2 )² + 16 = 0
Subtract 16 to both sides
- ( x + 2 )² = - 16
Multiply both sides by - 1
( x + 2 )² = 16
x + 2 = ± √16
x + 2 = ± 4
Subtract 2 to both sides
x = ± 4 - 2
The solutions are:
p = 4 - 2 = 2
q = - 4 - 2 = - 6
f(x) = ( - 1 ) ( x - p ) ( x - q )
f(x) = - ( x - 2 ) [ ( x - ( - 6 ) ]
f(x) = - ( x - 2 ) ( x + 6 )
Express f(x) = - x² - 4 x + 12
then
add and subtract 4 to left side
f(x) = - x² - 4 x + 12 + 4 - 4
f(x) = - x² - 4 x - 4 + 12 + 4
f(x) = - ( x² + 4 x + 4 ) + 16
f(x) = - ( x² + 2 ∙ x ∙ 2 + 2² ) + 16
Since:
( a + b )² = a² + 2 ∙ a ∙ b + b²
( x + 2 )² = x² + 2 ∙ x ∙ 2 + 2²
f(x) = - ( x + 2 )² + 16
f(x) = a ( x - p ) ( x - q )
where p and q are the roots:
In this case:
a = - 1
- ( x + 2 )² + 16 = 0
Subtract 16 to both sides
- ( x + 2 )² = - 16
Multiply both sides by - 1
( x + 2 )² = 16
x + 2 = ± √16
x + 2 = ± 4
Subtract 2 to both sides
x = ± 4 - 2
The solutions are:
p = 4 - 2 = 2
q = - 4 - 2 = - 6
f(x) = ( - 1 ) ( x - p ) ( x - q )
f(x) = - ( x - 2 ) [ ( x - ( - 6 ) ]
f(x) = - ( x - 2 ) ( x + 6 )